EVALUATION OF ANTI-OBESITY EFFECT OF AQUEOUS EXTRACT OF MUCUNA PRURIENS SEEDS ON RATS - Mansuri, Javid; Paranjape, Archana (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Evaluation of the anti-obesity effect of aqueous extract of Mucuna pruriens seeds on rats. Methods: Male Sprague-Dawley (SD) rats were subjected to high-fat diet (HFD) for 12 wk. L-DOPA (12.5 mg/kg, p. o.) as standard drug and aqueous extract of Mucuna pruriens (AEMP) seeds (200 mg/kg, p. o. and 400 mg/kg, p. o.) as test drugs were administered in last 4 wk along with HFD. Body weight, food intake, body mass index (BMI), serum total cholesterol (TC), triglyceride (TG) and high-density lipoprotein (HDL) levels were measured at the end of fourth, eighth and twelfth wk, while white adipose tissue (WAT) mass and brain dopamine levels were measured at the end of the twelfth wk. Results: AEMP (200 mg/kg, p. o.) and (400 mg/kg, p. o.) treated groups showed a significant decrease in food intake and weight gain without altering BMI. Moreover, TG levels were lower in treated groups as compared to the HFD group, but no significant changes were observed in TC and HDL levels. L-DOPA-treated group showed a significant decrease in body weight, food intake, BMI and WAT. Both AEMP and L-DOPA-treated groups showed an increase in brain dopamine levels as compared to disease control group (p<0.05). Conclusion: L-DOPA and AEMP showed anti-obesity activity by reducing body weight gains, food intake and WAT weights; modulating TG with increased brain dopamine level which correlates to the inhibitory action of dopamine on reward mechanism.Â